Strategy for Developing Entrepreneurial Business of Cincau Ice Drink in Unaaha City - Leni Saleh; Sarty Syarbiah (Proceeding of The International Conference on Economics and Business, 2023)
The purpose of this study is to analyze the development strategy in the grass jelly drink business as an effort to make the grass jelly ice drink business a strong and competitive business so that the business is able to create added value for the surrounding environment as well as for grass jelly drink entrepreneurs. In the ice jelly drink business development strategy, the techniques used as data collection are primary and secondary data, namely by conducting interviews, distributing questionnaires and processing data. The first stage is to input data to determine the value of IFAS and EFAS, then use the SWOT matrix to find alternative strategies. Based on the research results, the grass jelly drink business business has 5 strengths, 5 weaknesses, 5 opportunities and 4 threats. The strategy for developing the grass jelly drink business is in quadrant I, indicating that the grass jelly drink business faces an environment that has relatively greater opportunities to overcome its weaknesses, namely in the position of the Strength-Opportunity (SO) strategy. This position provides an indication that there is an opportunity for business development to be carried out, and has a strong position to develop.